Aukštieji kursai - pirmoji nepriklausomos Lietuvos aukštoji mokykla - Mančinskas, Česlovas (Lietuvos istorijos studijos, 1996)
After the newly independent Lithuanian state had been established, the necessity of development of economics, education, culture, and the state governing machinery became obvious. So the society needed a sufficient amount of educated specialists, which, at this moment, especially with a higher education, had only been a few. Because of the Russian tsarist governmental politics of national oppression, and having no higher school, the country remained undeveloped for almost a century. According to the data of the first general census of the population, only 42.18% of the population of Lithuania were literate, 25.18% were half-literate, and the others were illiterate persons.In 1919 the Lithuanian government decided not to establish a national higher school and to send young people for education to foreign higher schools. On 27 January, 1920, the Lithuanian intelligentsia of a democratic orientation decided to establish and financially support the first private higher school in Kaunas — "The Higher Courses." Z. Žemaitis was the first head of them, and J. Vabalas-Gudaitis, the next one. There were 6 departments (faculties): Humanitarian, Law, Mathematical-Physical, Technical, and Medical at the Courses, and they were headed by the deans E. Volteris, A. Janulaitis, Z. Žemaitis, T. Ivanauskas, J. Šimoliūnas, and M. Nasvytis. There were 522 unattached students and 34 lecturers.